Pengembangan Sistem Informasi Berita Berbasis Website Untuk Polsek Kuta Selatan - Gagas Pradipta Jatmiko; I Putu Gede Hendra Suputra (Jurusan Informatika, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Udayana, 2026)
An official website has become an essential need for public institutions such as Polsek Kuta Selatan, especially to provide access to information related to security and public services in one of Bali's main tourist areas. The development of this website aims to enhance communication effectiveness between Polsek Kuta Selatan and the community, as well as to build a positive image and increase public trust. The website features a main page displaying the latest news, contact information, and emergency numbers. A news search feature allows users to access information related to police activities easily. For admins, there is a dashboard that enables efficient news management, including adding, editing, and deleting news content. The interface design is responsive, making it easily accessible on both mobile and desktop devices. Black Box testing indicates that all system functions operate successfully with the expected output. Additionally, a System Usability Scale (SUS) test, involving a questionnaire with 34 respondents aged 21-55, resulted in an average SUS score of 86,617. With this website, Polsek Kuta Selatan can improve the quality of public services, transparency of information, and strengthen relations with the community to create a safer and more conducive environment.